Voltammetry of osmium-modified DNA at a mercury film electrode: application in detecting DNA hybridization - Kostecka, Pavel; Havran, Ludek; Pivonkova, Hana; Fojta, Miroslav (Bioelectrochemistry (Amsterdam, Netherlands), 2004)
Mercury film electrodes (MFE) have recently been used in nucleic acid electrochemical analysis as alternatives to the classical mercury drop ones. DNA modified with osmium tetroxide, 2,2'-bipyridine (Os,bipy) can be detected with a high sensitivity at mercury electrodes via measurements of a catalytic osmium signal. In this paper we show that mercury film on a glassy carbon electrode can be used in voltammetric analysis of Os,bipy-modified DNA. Application of the MFE as a detection electrode in double-surface electrochemical DNA hybridization assay involving osmium labeling of target DNA is demonstrated.
Keywords: Nucleic Acid Hybridization; DNA sondy; Electrochemistry; DNA Probes; Staining and Labeling; barvení a značení; biosenzitivní techniky; biokompatibilní potahované materiály; 2,2'-dipyridyl; elektrody; 2,2'-Dipyridyl; Biosensing Techniques; rtuť; hybridizace nukleových kyselin; Coated Materials, Biocompatible; organokovové sloučeniny; Electrodes; Mercury; Organometallic Compounds; elektrochemie; DNA